Transnational collective bargaining at company level: a new component of European industrial relations? - Schömann, Isabelle; Jagodziñski, Romuald; Boni, Guido; Clauwaert, Stefan; Glassner, Vera; Jaspers, Teun (Brussels, 2012)
"Transnational collective bargaining (TCB) has become a ‘hot’ topic of European industrial relations. As well as collective bargaining between workers and employers conducted at the sectoral or national level, negotiations on employee rights and working conditions now also take place at the supranational level, within multinational companies. It is a development that poses major challenges for trade unions, as well as for employers and lawmakers. This book takes stock of the particular challenges faced by trade union representatives, works councils and employer organisations; it reviews the existing literature on this topic and examines contrasting views of the prospects for subsequent development of this new practice; it also offers some practical suggestions for policymakers who find themselves having to deal with this new component of the Europeanisation of industrial relations. One of the key questions tackled in the book is whether a regulatory framework for TCB is feasible, necessary and/or useful. Perhaps even more importantly: can we, given the proliferation of instances of TCB, actually manage without such a legal system, and what should be the main elements of such a framework? By providing a better understanding and a critical analysis of the emergence and development of transnational collective bargaining, the authors of this book offer valuable help to trade unionists and practitioners in preparing for – and being prepared for – this next stage in the internationalisation of industrial relations."